ANALISIS RISIKO DALAM KEPUTUSAN INVESTASI - Wardiningsih, Suprihatmi Sri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT In investment decisions, management must deal with uncertainty in the future. The uncertainty of a number of possible events can occur. Risk management is what needs to be considered in investment decisions. Management needs to incorporate an element of risk in the investment proposals of thinking, so that each investment project has a different risk levels. This will affect the required rate of return (Required Rate of Return), which determines whether a feasible investment project is accepted or rejected. Approach to the measurement of risk in investment decisions, among others: the mean standard deviation approach, certainty equivalent approach, risk adjusted discount rate approach, sensitivity analysis, scenario analysis, break even analysis. Keywords: Risk analysis, risk measurement, Investment Decisions, Certainty Equivalent